Pericyte heterogeneity identified by 3D ultrastructural analysis of the microvessel wall - Abdelazim, Hanaa; Payne, Laura Beth; Nolan, Kyle; Paralkar, Karan; Bradley, Vanessa; Kanodia, Ronak; Gude, Rosalie; Ward, Rachael; Monavarfeshani, Aboozar; Fox, Michael A.; Chappell, John C. (Frontiers in Physiology, 2022)
Confident identification of pericytes (PCs) remains an obstacle in the field, as a single molecular marker for these unique perivascular cells remains elusive. Adding to this challenge is the recent appreciation that PC populations may be heterogeneous, displaying a range of morphologies within capillary networks. We found additional support on the ultrastructural level for the classification of these PC subtypes – “thin-strand” (TSP), mesh (MP), and ensheathing (EP) – based on distinct morphological characteristics. Interestingly, we also found several examples of another cell type, likely a vascular smooth muscle cell, in a medial layer between endothelial cells (ECs) and PCs harboring characteristics of the ensheathing type. A conserved feature across the different PC subtypes was the presence of extracellular matrix (ECM) surrounding the vascular unit and distributed in between neighboring cells. The thickness of this vascular basement membrane was remarkably consistent depending on its location, but never strayed beyond a range of 150-300nm unless thinned to facilitate closer proximity of neighboring cells (suggesting direct contact). The density of PC-EC contact points (“peg-and-socket” structures) was another distinguishing feature across the different PC subtypes, as were the apparent contact locations between vascular cells and brain parenchymal cells. In addition to this thinning, the ECM surrounding EPs displayed another unique configuration in the form of extensions that emitted out radially into the surrounding parenchyma. Knowledge of the origin and function of these structures is still emerging, but their appearance suggests the potential for being mechanical elements and/or perhaps signaling nodes via embedded molecular cues. Overall, this unique ultrastructural perspective provides new insights into PC heterogeneity and the presence of medial cells within the microvessel wall, the consideration of ECM coverage as another PC identification criteria, and unique ECM configurations (i.e. radial extensions) that may reveal additional aspects of PC heterogeneity.